Effect of ractopamine and Cr-yeast supplementation on leptin levels, haematological variables and fatty acid profile in pigs - Trujillo, Luis Guillermo (2023)
The aim of this study was to determine the effect of ractopamine (RAC) and chromiumyeast (Cr-Lev) on the fatty acid profile, haematological parameters and serum leptin levels in finishing pigs. For this, 20 pigs of 63.2 ± 7.6 kg and 118 days of age were assigned to four treatments during the last 30 days of fattening. The treatments were T1: control group with basic food; T2: addition of 10 ppm/kg of RAC, and T3 and T4 with 0.2 and 0.4 ppm/kg of Cr-Lev without addition of RAC, respectively. Serum leptin levels were quantified at days 15 and 30, backfat thickness at day 30, and haematological analysis at days 0, 15, and 30 of the study. In addition, the profile of fatty acids in the meat was determined by gas chromatography. A completely randomized design with five replicates was used. The treatments affected the serum leptin concentration at 15 days (p<0.05), but not at 30 days. Leptin concentrations between measurement days within treatments did not show significant differences. The haematological values remained constant and the thickness of the backfat did not vary between treatments. The fatty acid profile of the meat varied between treatments (p<0.05), with the lowest values in T2 and the highest in T4, especially linoleic and arachidonic acids. Fatty acids were positively correlated (r>0.6) with each other, but not with backfat thickness, nor with leptin.